Stories of pirates - Punter, Russell; Fox, Christyan (Usborne Publishing London, 2015)
Prepare to set sail with the craziest crew of pirates on the Seven Seas. Will Charlie get rid of his pesky parrot? Can Molly escape the clutches of the sneaky Captain Spike? And just how will Sam reveal the identity of the Masked Pirate? Come aboard and find out! Part of the Usborne Reading Programme developed with reading experts at the University of Roehampton, specially written for children just starting to read alone. "Irresistible for children learning to read." - Child Education Plus